2017
DOI: 10.1038/s41598-017-04818-y
|View full text |Cite
|
Sign up to set email alerts
|

ANKRD22 promotes progression of non-small cell lung cancer through transcriptional up-regulation of E2F1

Abstract: Lung cancer is the leading cause of death among all malignancies due to rapid tumor progression and relapse; however, the underlying molecular mechanisms of tumor progression are unclear. In the present study, we identified ANKRD22 as a novel tumor-associated gene in non-small cell lung cancer (NSCLC). According to the clinical correlation analysis, ANKRD22 was highly expressed in primary cancerous tissue compared with adjacent cancerous tissue, and high expression levels of ANKRD22 were significantly correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…High expression of SGLT1, which is encoded by SLC5A1, is associated with tumor development and poor prognosis in ovarian cancer [75]. In addition, ANKRD22 promotes progression of non-small-cell lung cancer [76]. However, higher ANKRD22 expression levels in prostate cancer are associated with longer DFS following radical prostatectomy [77].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of SGLT1, which is encoded by SLC5A1, is associated with tumor development and poor prognosis in ovarian cancer [75]. In addition, ANKRD22 promotes progression of non-small-cell lung cancer [76]. However, higher ANKRD22 expression levels in prostate cancer are associated with longer DFS following radical prostatectomy [77].…”
Section: Discussionmentioning
confidence: 99%
“…Typhi (Salerno‐Goncalves et al , ). C1QB and C1QC are well‐known subunits of the complement subcomponent C1q and, together with ANKRD22 [involved in cell cycle control (Yin et al , )], have previously been described as part of a signature able to distinguish active from latent TB (Kaforou et al , ). The function of the transcription factor RFX7 is largely unknown but has been found to be strongly up‐regulated during blood‐stage malaria, and its selection in our 7‐gene signature is therefore likely to be driving the classification of malaria cases.…”
Section: Discussionmentioning
confidence: 99%
“…While ALDH1A1 has not specifically been linked with responses to invasive bacterial infections, it is involved in gut-homing of TCs through expression of retinoic acid (Molotkov & Duester, 2003;Iwata et al, 2004), a phenotype we have observed following infection with S. Typhi (Salerno-Goncalves et al, 2017). C1QB and C1QC are well-known subunits of the complement subcomponent C1q and, together with ANKRD22 [involved in cell cycle control (Yin et al, 2017)], have previously been described as part of a signature able to distinguish active from latent TB (Kaforou et al, 2013a). The function of the transcription factor RFX7 is largely unknown but has been found to be strongly up-regulated during blood-stage malaria, and its selection in our 7-gene signature is therefore likely to be driving the classification of malaria cases.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 While ALDH1A1 has not specifically been linked with responses to invasive bacterial infections, it is involved in gut-homing of TCs through expression of retinoic acid, 46,47 a phenotype we have observed following infection with S. Typhi. 26 C1QB and C1QC are well-known subunits of the complement subcomponent C1q and, together with ANKRD22 (involved in cell cycle control 48 ), have previously been described as part of a signature able to distinguish active from latent TB. 17 The function of the transcription factor RFX7 is largely unknown, but has been found to be strongly up-regulated during blood stage malaria and its selection in our 7-gene signature is therefore likely to be driving the classification of malaria cases.…”
Section: Discussionmentioning
confidence: 99%